Can spraying tip and tank mix affect weed control and herbicide selectivity in onion culture? - Comachio, Lucas Boaretto; Rossi, João Pedro Rech; Amler, Dionatan Alan; Amler, Fabrício Fábio; Guerra, Naiara; Mendes de Oliveira Neto, Antonio (Revista de Ciências Agroveterinárias, 2024)
This paper aimed the evaluation of weed control in Juporanga onion, transplanted by cuttings, regarding spray tips and herbicide tank mixture. It was conducted in a commercial area in Imbuia municipality, in SC, Brazil. Randomized block experimental design was used, with treatments organized in factorial scheme (2 x 4) + 2, and four repetition. The treatments consisted in two spraying tips models: TT 110 015 and ADIA 110 02, and four herbicide mixtures: ioxynil + flumioxazin (IO + FL), ioxynil + pendimethalin (IO + PE), diuron + flumioxazin (DI + FL) and diuron + pendimethalin (DI + PE). Additionally, two controls, with and without deweeding were kept. Assessed variables were low amaranth, common sowthistle, lady’s thumb and swinecress control; phytotoxicity, plant stand, bulb’s diameter and average weight and, commercial and total yield. Treatments were effective controlling low amaranth, common sowthistle and lady’s thumb. Swinecress’s controls were lower than 81% for DI + PE treatment applied with ADIA 110 02 spraying tip. The phytotoxicity was higher than 18% at 7 days after spraying (DAS) and 8% at 14 DAS for treatments with IO + FL and DI + FL. Spraying tips and herbicide tank mixtures did not influence yield components or bulb productivity. All tank mixtures were efficient to controlling weed plants, and selective for onion crop, regardless the spraying tip.